Catalytic performance enhancement of CaO by hydration-dehydration process for biodiesel production at room temperature. (1st June 2018) - Roschat, Wuttichai; Phewphong, Sunti; Thangthong, Amonrat; Moonsin, Preecha; Yoosuk, Boonyawan; Kaewpuang, Teadkait; Promarak, Vinich
Graphical abstract: CaOHy can be utilized as high efficient heterogeneous solid catalyst for transesterification of palm oil to biodiesel at room temperature. Highlights: Hydration-dehydration process can improve the catalytic activity of CaO. Over 94% FAME yield is achieved under optimization of reaction conditions at room temperature. CaOHY exhibits high potential as solid catalyst for low cost industrial biodiesel production. Abstract: This research presents an efficient technique to enhance the catalytic activity, surface area and total basicity of CaO with hydration-dehydration process to be the catalyst for the transesterification of palm oil to biodiesel. The catalytic performance of the resulted catalyst was tested via transesterification reaction of palm oil at room temperature (30 ± 2 °C) and was compared against commercial CaO and CaO derived from natural calcium carbonate sources. Under the optimal reaction conditions (catalyst loading of 5 wt%, methanol to oil molar ratio 12:1), FAME yields were approximately 94% for CaOHY and 60.5%, 55.3%, 49.5% and 51.4% for CaOcom, CaOegg, CaOgol and CaOriv as catalysts, respectively. Catalyst reusability and scaling up of biodiesel production from 50 mL to 1.5 L were also investigated. The obtained biodiesel product after purification and treatment process showed high quality fuel properties within the range of biodiesel standard and similar with high-speed diesel. Furthermore, the used CaOHY as a solid heterogeneous catalyst at room temperature was not only low-cost but also environmentally-friendly, showing a high potential in the biodiesel production.